2023
DOI: 10.1039/d3nr02175k
|View full text |Cite
|
Sign up to set email alerts
|

Efficient mRNA delivery using lipid nanoparticles modified with fusogenic coiled-coil peptides

Ye Zeng,
Mengjie Shen,
Roy Pattipeiluhu
et al.

Abstract: Gene delivery has great potential in modulating protein expression in specific cells to treat diseases. Such therapeutic gene delivery demands sufficient cellular internalization and endosomal escape. Of the various nonviral...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 74 publications
0
5
0
Order By: Relevance
“…Finally, a cytotoxicity assay revealed no significant differences in the cytotoxicity between CPE4- and unfunctionalized LNPs. Altogether, these results showed that poor endosomal escape can be avoided by LNP internalization through CPE4/CPK4-induced membrane fusion, resulting in high transfection efficiency and enhanced mRNA expression in vitro …”
Section: Lipid-based Nanoparticles Functionalized With Fusogenic Pept...mentioning
confidence: 76%
See 3 more Smart Citations
“…Finally, a cytotoxicity assay revealed no significant differences in the cytotoxicity between CPE4- and unfunctionalized LNPs. Altogether, these results showed that poor endosomal escape can be avoided by LNP internalization through CPE4/CPK4-induced membrane fusion, resulting in high transfection efficiency and enhanced mRNA expression in vitro …”
Section: Lipid-based Nanoparticles Functionalized With Fusogenic Pept...mentioning
confidence: 76%
“…The lipopeptide-based fusion system CPE/CPK has already been used in many applications, such as cell sorting, liposome fusion, ,, liposome cell fusion, ,, lipid nanoparticle cell fusion, cell–cell fusion, and anion transporter delivery to membranes …”
Section: Fusogenic Peptidesmentioning
confidence: 99%
See 2 more Smart Citations
“…There are several biomaterial designs and modifications that show promise for the safe delivery of mRNA, including lipids, lipid-like materials, polymers, and inorganic nanoparticles . Currently, lipid nanoparticles (LNPs) are the state-of-the-art vector for packaging, protecting, and releasing mRNA molecules within cells, as evidenced by the success of two COVID-19 mRNA-LNP vaccine formulations that received FDA approval in 2020. LNPs are typically composed of four lipid componentsan ionizable lipid, cholesterol, a helper lipid, and a poly­(ethylene glycol)-lipid conjugate, which can be varied to produce distinct formulations with desired physicochemical properties. However, the efficacy of LNPs in transfecting cells is limited by their ability to induce endo/lysosomal escape since they enter cells through endocytosis and are subjected to endolysosomal trafficking . Typically, less than 5% of the intracellularly delivered dose of mRNA by LNPs is able to reach the cytoplasm .…”
Section: Introductionmentioning
confidence: 99%